Betaine Supplementation Improves the Production Performance, Rumen Fermentation, and Antioxidant Profile of Dairy Cows in Heat Stress - Ali Mujtaba Shah; Jian Ma; Zhisheng Wang; Huawei Zou; Rui Hu; Quanhui Peng (Animals, 2020)
The aim of the current research was to investigate the effects of betaine (Bet) supplementation on the production performance, rumen fermentation, digestibility, and serum indexes of dairy cows. Thirty healthy Holstein cows with the same parity (milk production = 22 ± 2.5 kg) were randomly selected and divided into three groups. One group served as a control group (CON; no betaine); the other two groups were Bet1 (15 g/d per cow) and Bet2 (30 g/d per cow). All cows were fed regularly three times a day at 06:00, 14:00, and 22:00 h. Cows received the formulate diet, and water was provided ad libitum. The experiment lasted for 60 days during the summer season. Results showed that the dry matter intake, milk protein, and fat of Bet1 cows was significantly higher (p < 0.05) than that in other groups. The content of volatile fatty acid (VFA) in Bet1 was significantly higher (p < 0.05) than CON. Consistent with VFA, a similar trend was found in acetate, while propionate exhibited an opposite trend. Compared to other groups, the microbial protein (MCP) concentrations of Bet1 increased (p < 0.05). The apparent digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) of Bet1 was significantly higher (p < 0.05) than CON. The serum concentration of total antioxygenic capacity (T-AOC) in Bet1 and Bet2 was significantly increased (p < 0.05). Furthermore, the contents of malonaldehyde (MDA) and superoxide dismutase (SOD) in Bet2 were higher (p < 0.05) than that in other groups. Compared to CON and Bet2, Bet1 significantly increased (p < 0.05) the serum concentrations of glucose. Therefore, it is practicable to feed betaine to lactating cows to improve their performance in heat stress.